SWOT–CAME Analysis for Strengthening Transnational Research on Women in Engineering: The Case of the CAL Matilda Research Committee - Garcia De Cajen, Silvia; Montoya-Noguera, Silvana; Contreras-Ortiz, Sonia Helena; Erck, Isolda Mercedes (LACCEI, 2025)
The Research Committee of the Latin American Open Chair Matilda and Women in Engineering (CI-CAL) is a volunteer-based organization that brings together representatives from various Latin American and Caribbean countries. Over its four years of existence, this committee has generated knowledge and initiatives that have had a significant impact and are recognized in the region. This paper presents a case study aimed at conducting a diagnostic evaluation of CI-CAL, analyzing its strengths, weaknesses, opportunities, and threats (SWOT), as well as developing a prospective that includes strategies to correct, address, maintain, and exploit (CAME) factors that require attention, with a view to strengthening its consolidation as a Transnational Research Group on "Women in Engineering." This study is based on a collaborative approach that includes the application of SWOT analysis to identify and prioritize key factors, complemented by the use of the CAME tool to formulate strategies. The results obtained are relevant for CI-CAL to make informed decisions about the strategic actions to be implemented in its internal and external dynamics, thus contributing to the advancement and strengthening of the group in its mission to generate knowledge that contributes to promoting gender equality in the field of engineering.